HOW DO SPORTS COMPETITIONS HELP IN THE PROCESS OF SOCIALIZATION OF STUDENTS (10-12 YEARS OLD) - Ioan Sabin SOPA; Marcel POMOHACI; Dan Alexandru SZABO (Editura Universităţii din Oradea, 2018)
Our study focused on observing the influence of sports competitions and motor activities on pupils aged between 10 and 12. The experiment started in september 2016 and was finished in june 2017, and had as samples two groups of children, the first group, the experimental group, consisted of 20 students aged between 10 and 12 years old, 12 boys and 8 girls, with whom we dealt with the 2 hours of physical education and sports from the curriculum and 3 more training sessions on initiation in basketball game; the second group, the control group, consisting of 20 pupils aged between 10 and 12 years old, 13 boys and 7 girls, with whom we spent 2 hours of physical education following the classical curriculum. The research methods were the study of the specialized bibliography, the observation method with observation sheets of pupils' behavior, the graphic and mathematical methods.The results of the research showed significant differences between the two groups of pupils in the adaptation parameters to the school environment, the degree of integration in the school, the level of communication, the behavior at the lesson, and the work style; regarding the item of participation in group life, we found insignificant differences.